2006
DOI: 10.1177/0310057x0603400110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 3-in-1 Continuous Femoral Block of Differing Concentrations Compared to Patient Controlled Intravenous Morphine for Post Total Knee Arthroplasty Analgesia and Knee Rehabilitation

Abstract: We assessed the effectiveness of the 3-in-1 continuous femoral block as a form of postoperative pain relief for unilateral total knee arthroplasty (TKA). Sixty patients undergoing elective unilateral TKA under subarachnoid block were randomized into three groups. Postoperative analgesia was provided with a continuous 3-in-1 femoral nerve catheter with 0.15% ropivacaine in group A, a continuous 3-in-1 femoral nerve catheter with 0.2% ropivacaine in group B, or patient controlled intravenous morphine in group C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 22 publications
2
48
0
3
Order By: Relevance
“…One study demonstrated a significant increase in obturator motor blockade at 6 hours postoperatively [33]. Urinary retention was registered in one trial [35], cardiac events in one [38] and hypotension in two [35, 37]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated a significant increase in obturator motor blockade at 6 hours postoperatively [33]. Urinary retention was registered in one trial [35], cardiac events in one [38] and hypotension in two [35, 37]. No significant differences between active and control groups were reported.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Analgesic benefits of peripheral nerve blocks are well described. [45678910] Femoral nerve block, single shot or continuous (CFNB), also in combination with sciatic and/or obturator block is proven to provide superior analgesia to opioids alone. [111213] The main problems with these peripheral nerve blocks are prolonged muscle weakness, the risk of falling during exercise, and decubitus on pressure points, as described after sciatic nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Epidural analgesia and peripheral nerve blocks are frequently being used. They provide superior analgesia than opioids,[45678910111213] but cause muscle weakness, and risk of falling,[1415] postponing the physiotherapy exercises, and prolonging the hospital stay. Local infiltration analgesia (LIA) has lately gained popularity.…”
Section: Introductionmentioning
confidence: 99%
“…Die Notwendigkeit einer zusätzlichen Blockade des N. ischiadicus zur Komplettierung der Analgesie wird kontrovers diskutiert [1,3,5,9,21,25].…”
Section: Schmerztherapie Mit Stimulationskathetern Bei Kniegelenkersaunclassified
“…In einer Arbeit von Neuburger et al [19] wird für kontinuierlich anteriore Ischiadikuskatheter eine Dislokationsrate von 1,4% beschrieben, in anderen Arbeiten für Femoraliskatheter 2,8% [11] bis 7,9% [25].…”
Section: Introductionunclassified